Fenomena Simplifikasi dan Desofistikasi Budaya Jawa di luar Jawa - Anharudin, A; Elizabeth, Misbah Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
Culture will change with place and time. As a culture, Javanese culture has a tight characteristic. It is interesting to observe the culture among the Javanese community in Lampung which showed the desophistication in Javanese culture that they applied on. The term of ?desophistication? in this context meant the loss of the sophisticated traits of Javanese culture or the lost original traits of Javanese culture as in Java mainland. The study was done by applying qualitative research, and the data were combined by involving intensively in the daily life of Javanese people within Javanese communities in Lampung, mainly those who had moved to these areas through the processes of colonization and transmigration, and their inheritances. This study uses an assumption that Javanese culture in the mainland of Java is very sophisticated, with the characteristics of